Stimulation of Maize Growth and Development and Improvement of Soil Properties Using New Specialised Organic-Mineral Materials - Marzena S. Brodowska; Mirosław Wyszkowski; Ryszard Grzesik (Molecules, 2025)
The use of mineral fertilisers has increased in recent years, but this has had a negative effect on the environment, including causing the water in rivers and lakes to become too rich in nutrients, a process known as eutrophication. Current research focuses on producing fertiliser materials that are environmentally friendly. The aim of this study was to examine the impact of novel specialised organic-mineral fertilisers (OMFs: NP 24-12, NP 10-10, and NP 10-10 Zn+) on the yield and chemical composition of maize. These fertilisers were compared with a control (no fertiliser) and with other fertilisers (mixture of commercial fertilisers (MCFs): NP 24-12 and NP 10-10) that were used as a reference. All fertilisers increased the SPAD index at the fifth leaf unfolded stage of maize, with the majority (apart from OMF NP 10-10) also increasing it at the panicle emergence stage. MCF NP 10-10 had the most positive effect on the plant height, while OMF NP 10-10 had the least positive effect. All fertilisers had a positive effect on maize growth and development, with MCFs NP 10-10 and NP 24-12 having by far the strongest effect on increasing crop yields. The yield of plants fertilised with OMFs NP 24-12, NP 10-10, and NP 10-10 Zn+ was lower than the yields of plants fertilised with MCF NP 24-12 and MCF NP 10-10. OMF NP 10-10 caused a greater increase in the contents of all elements, and OMF NP 24-12 caused a greater increase in most elements (except P and Ca) in maize than MCFs did at an identical NP ratio. OMF NP 10-10 Zn+ was found to have a significant impact on the mineral composition of maize, resulting in a decline in Ca and P levels, along with a notable increase in Mg, Zn, and Cu concentrations. The most significant differences were observed for Cu and Zn. The OMFs, notably NP 24-12 and NP 10-10, exhibited a comparatively diminished acidifying impact in comparison with the MCFs. The application of fertilisers resulted in a significant increase in soil nutrient levels, with most fertilisers increasing the soil N, P, and Zn contents. Additionally, the OMFs led to an increase in Cu. However, MCFs NP 24-12 and NP 10-10 reduced the soil Cu and Mn contents. Studies should include other species as they have different needs. Field experiments are also needed.